PERANAN PROGRAM SERTIFIKASI DAI MUI DALAM UPAYA PENGUATAN PENDIDIKAN MODERASI BERAGAMA - Ahwani, Muhamad Alfan; Hasiolan (Prodi Magister Pendidikan Agama Islam (MPAI) - STAI Nida El-Adabi Bogor, 2025)
The Dai Certification Program, organized by the Indonesian Ulama Council (MUI), aims to enhance the competence of preachers in delivering moderate and inclusive sermons. This research uses a descriptive qualitative literature study approach aimed at analyzing the role of the program in strengthening religious moderation in Indonesia, particularly amidst the challenges of globalization, societal pluralism, the rise of radicalism, and the increasing potential for religion-based conflicts. The findings of this research indicate that this program provides a better understanding of the principles of religious moderation and teaches preachers adaptive preaching methods to the local context. This certification also increases public trust in certified preachers. However, it was found that expectations did not match reality, namely, the minimal participation of preachers in this certification program, due to disagreements with the concept of moderation and group fanaticism. Similarly, there are challenges in the implementation of religious moderation, such as radicalization and extremism, which are threats to religious moderation, conflicts, and the role of moderation in balancing interfaith perspectives. Overall, this program plays a crucial role in building an inclusive and harmonious framework for preaching. To enhance the national impact of the program, these findings recommend the development of a broader program and collaboration with various stakeholders.